PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. OMEGA MAS PASURUAN - Fahmi, Syaifuddin (Jurnal Ekonomi Modernisasi, 2016)
Aims of this study was to determine the effect of work stress and work conflict on the work spirit  of employees at PT. Omega Mas Pasuruan. This study uses a quantitative approach to survey research method, the research took a sample from a population and using questionnaires as a means of collecting primary data. The population in this study were all employees of PT. Omega Mas Pasuruan which amounted to 77 employees, by using census methode,a sample of this study are the entire population. The results showed that job stress has negative effects on work spirit, Labor conflict has  negative effects on work spirit and  labor conflict is the variable most dominant influence on work spirit.